A new definite linear algorithm for the structural equation model with application in fire risk evaluation. Issue 23 (1st December 2016) - Ding, Qian; Tong, Qiaohui; Tong, Qiaoling; Zou, Xuecheng; Tong, Hengqing
ABSTRACT: A definite linear algorithm based on the constraint least squares solution for the structural equation model (SEM) is proposed. First, the modular constraint least squares solution is obtained. Then, the prescription constraint (the weight coefficients are non negative and their sum is one) is added, and the last solution of SEM is obtained. This definite linear algorithm is a new and reasonable algorithm compared to traditional algorithms like linear structural relationship (LISREL) and partial least squares (PLS). Finally, the application of SEM with the definite linear algorithm in fire risk evaluation is addressed, and the data example is calculated using software Data Analysis and Statistical Computation (DASC).